2021
DOI: 10.1049/cit2.12060
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning for time series forecasting: The electric load case

Abstract: Management and efficient operations in critical infrastructures such as smart grids take huge advantage of accurate power load forecasting, which, due to its non-linear nature, remains a challenging task. Recently, deep learning has emerged in the machine learning field achieving impressive performance in a vast range of tasks, from image classification to machine translation. Applications of deep learning models to the electric load forecasting problem are gaining interest among researchers as well as the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(59 citation statements)
references
References 74 publications
0
58
0
1
Order By: Relevance
“…The success of the method is mainly due to the following three reasons [ 9 , 28 , 41 , 50 , 51 ]: Local connectivity: One set of input neurons is connected to each hidden neuron (according to a specific space-time metric). Compared to a fully linked network, this feature significantly reduces the number of parameters that must be learned and facilitates calculations.…”
Section: Methodsmentioning
confidence: 99%
“…The success of the method is mainly due to the following three reasons [ 9 , 28 , 41 , 50 , 51 ]: Local connectivity: One set of input neurons is connected to each hidden neuron (according to a specific space-time metric). Compared to a fully linked network, this feature significantly reduces the number of parameters that must be learned and facilitates calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly to renewable energy production forecasting, the state-of-the-art approaches for predicting the residential electricity load in the short term are mostly related to deep learning techniques with preprocessed augmented data: RNN, CNN, and transformers [25,26,27,28,22].…”
Section: Consumption Forecastingmentioning
confidence: 99%
“…As in other fields, deep learning approaches are getting more attention from researchers lately. An unpublished review of deep learning approaches can be found in [78]. It is not limited to the LV-level but they explicitly compare deep learning approaches applied to household data.…”
Section: Related Reviewsmentioning
confidence: 99%